(untitled) (INTERNATIONAL SCIENTIFIC E-CONFERENCE " INNOVATIVE TRENDS IN SCIENCE, PRACTICE AND EDUCATION" – Ankara, Turkey, 2024)
In this article, one of the famous scientists of the Muslim world, Dr. Yusuf Muhammad As-Siddiqui, the account of his study of the Christian religion, has been described, including his critical views on the study of Christian sources. During the article, the reader will get acquainted with interesting information about the history and components of Christian religious sources.